2002
DOI: 10.1073/pnas.112202899
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive activation ofStat5aby retrovirus integration in early pre-B lymphomas of SL/Kh strain mice

Abstract: We found that the second intron of Stat5a was one of the common integration sites of the endogenous ecotropic murine leukemia virus, i.e., SL͞Kh virus integration-1 (Svi1), in early pre-B lymphomas in SL͞Kh mice. The high expression of STAT5A induced by Svi1 integration and activation accelerated the transcription of its target genes such as c-Myc. Transfection of the constitutively active Stat5a mutant cDNA, but not of the wild-type cDNA, to the bone marrow cells induced colony formation of pre-B cells in a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(77 citation statements)
references
References 23 publications
1
76
0
Order By: Relevance
“…59 The results presented here showing sustained STAT5 activation downstream of JAK2 as a crucial mediator of the hyperproliferative responses from truncated G-CSF-Rs associated with AML further emphasizes the importance of the JAK2-STAT5 module in malignancy -a role that has apparently been conserved throughout evolution. 59,60 This is perhaps not surprising given the important cell cycle regulators known to be stimulated by STAT5, including cyclin D1 61 and c-myc, 62 not to mention its positive effects on cell survival mediators, such as bcl-XL and bcl-2. 56,63 Together, this suggests that suppression of STAT5 function may represent an important general strategy in the treatment of leukemias and other cancers.…”
Section: Discussionmentioning
confidence: 99%
“…59 The results presented here showing sustained STAT5 activation downstream of JAK2 as a crucial mediator of the hyperproliferative responses from truncated G-CSF-Rs associated with AML further emphasizes the importance of the JAK2-STAT5 module in malignancy -a role that has apparently been conserved throughout evolution. 59,60 This is perhaps not surprising given the important cell cycle regulators known to be stimulated by STAT5, including cyclin D1 61 and c-myc, 62 not to mention its positive effects on cell survival mediators, such as bcl-XL and bcl-2. 56,63 Together, this suggests that suppression of STAT5 function may represent an important general strategy in the treatment of leukemias and other cancers.…”
Section: Discussionmentioning
confidence: 99%
“…10) After 72 h, colonial growth was observed only from the BM transfected with 1 * 6-Stat5a cDNA, but not with wild-type Stat5a cDNA or an empty vector (Fig. 1B).…”
Section: Provirus Integration and Molecular Mechanism Of Lymphomagenesismentioning
confidence: 99%
“…Phosphorylation signals for Stat5a come from the IL7-receptor and the pre-B cell receptors. Stimulation of Svi1 lymphoma cells with antibodies to IL7R 10) or Igα induced transient phosphorylation of Stat5a and thereby increased affinity to the GAS element and transcription of the target genes. Signaling through Igα is specifically inhibited by PP2, an inhibitor to Src kinase, but not by picetannol, an inhibitor to Syk kinase (Tasuruyama et al, unpublished observation).…”
Section: Provirus Integration and Molecular Mechanism Of Lymphomagenesismentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we aimed to establish an in vitro integration assay using www.intechopen.com HIV-1 Selectively Integrates Into Host DNA In Vitro 307 retroviral cDNA and integrase. Yoshinaga et al previously reported the development of an in vitro integration assay using recombinant HIV-1 integrase, and short viral and target DNA sequences [9]. Using this method, they successfully detected retroviral cDNA-target DNA complexes in vitro and reported that the dinucleotide motif 5'-CA that is located at the proviral genome termini was essential for HIV-1 integration.…”
Section: Introductionmentioning
confidence: 99%